The Counseling Communities in Buaran Village RT 001 / RW 005 on the Appropriate Use of Antibiotics: Penyuluhan Penggunaan Antibiotik yang Tepat pada Masyarakat di Kelurahan Buaran RT 001 / RW 005 - Saragih, Tanti Juwita; Fahriati, Andriyani Rahmah; Listiana, Ida; Nurihardiyanti, Nurihardiyanti; Amalia, Tania Rizki; Adharudin, M.; Putro, Wahyu Gito; Umar, Camila Putri; Aulia, Atina Fitri (Ruang Ide Publisher, 2022)
Abstract Antibiotics are one of the most commonly used drugs in the community because they are so readily available, even without a prescription. Utilizing antibiotics excessively, improperly, and unnecessarily promotes the emergence of resistance and even multiple resistances in certain bacteria, which can lead to cross-infection. According to numerous studies conducted in Indonesia regarding antibiotic knowledge, there are still a large number of people from various circles who do not comprehend the use of antibiotics. Resistance to the antibiotics ampicillin (73%), cotrimoxazole (56%), chloramphenicol (43%), ciprofloxacin (22%), and gentamicin (18%) resulted in 781 patients infected with Escherichia coli bacteria in 2016, according to research conducted by Nisak. In addition, the results of the research on knowledge of antibiotic use in the community revealed that as many as 14 respondents had low knowledge and only 20 respondents had high knowledge of antibiotic use among mothers in the Airlangga Village area of the Gubeng District of Surabaya. Therefore, we perform community service utilizing health education techniques regarding the correct use of antibiotics. The activity was conducted for 120 minutes on June 25, 2022 in Buaran Village, RT001/RW005, Pamulang, Banten, Indonesia. The success of community service activities is determined by administering pre- and post-tests. From pre-test results of 64.3% to post-test results of 90.7%, there was an increase of 26.4% in the percentage of the public who knew about the use of antibiotics. Keywords: Antibiotics, Resistance, Public Knowledge